Proximate Composition, Amino Acid Profile, and Mineral Content of Four Sheep Meats Reared Extensively in Morocco: A Comparative Study - Kamal Belhaj; Farid Mansouri; Abdessamad Ben moumen; Marianne Sindic; Marie-Laure Fauconnier; Mohamed Boukharta; Hana Serghini Caid; Ahmed Elamrani (The Scientific World Journal)
This study aimed to compare the organoleptic and nutritional quality of four sheep meats produced in Morocco. This comparison was carried out by analyzing the proximate composition, amino acid profile, and mineral content of meat. The majority of the evaluated parameters were influenced by genetic and geographical factors (p<0.05). The longissimus lumborum muscle had higher a∗ value in Timahdite and Ouled-Djellal breeds. The highest values of macroelement were recorded in samples of Beni-Guil meat sampled in the Tendrera region (BGT; 1067.3 mg/100 g), while the highest microelement content was registered in Timahdite meat (5.7 mg/100 g). Iron and zinc were the major identified trace elements, while phosphorus and potassium were the most abundant macroelements. The abundant amino acid was glutamic, while cysteine and methionine were least abundant. The higher essential amino acids index (IEAA) was recorded in the Timahdite sheep meat (162.20, 158.71, 161.02, and 159.65, respectively, for Timahdite, BGT, Ouled-Djellal breeds, and Beni-Guil meat sampled in Ain Beni Mathar region). From a nutritional point of view, the studied meats had a good protein and mineral quality, due to their richness in essential amino acids and microelements. The present study provided new insights on the organoleptic quality and the nutritional value of three Moroccan sheep meats reared in outdoor production system.